Effects of Trandolapril on Structural, Contractile and Electrophysiological Remodeling in Experimental Volume Overload Heart Failure - Jarkovská, Dagmar; Miklovič, Matúš; Švíglerová, Jitka; Červenka, Luděk; Škaroupková, Petra; Melenovský, Vojtěch; Štengl, Milan (Frontiers in Pharmacology, 2021)
Chronic volume overload induces multiple cardiac remodeling processes that finally result in eccentric cardiac hypertrophy and heart failure. We have hypothesized that chronic angiotensin-converting enzyme (ACE) inhibition by trandolapril might affect various remodeling processes differentially, thus allowing their dissociation. Cardiac remodeling due to chronic volume overload and the effects of trandolapril were investigated in rats with an aortocaval fistula (ACF rats). The aortocaval shunt was created using a needle technique and progression of cardiac remodeling to heart failure was followed for 24 weeks. In ACF rats, pronounced eccentric cardiac hypertrophy and contractile and proarrhythmic electrical remodeling were associated with increased mortality. Trandolapril substantially reduced the electrical proarrhythmic remodeling and mortality, whereas the effect on cardiac hypertrophy was less pronounced and significant eccentric hypertrophy was preserved. Effective suppression of electrical proarrhythmic remodeling and mortality but not hypertrophy indicates that the beneficial therapeutic effects of ACE inhibitor trandolapril in volume overload heart failure might be dissociated from pure antihypertrophic effects.